A method of the determination of hydrogeological parameters of the aquifers on the results of the experimental constant-rate pumping tests - M. M. Burakov (Известия высших учебных заведений: Геология и разведка, 2017)
On the basis of the approximate solution of the problem of groundwater filtration during the experimental constant-rate pumping tests of the pressure aquifers, a method for the processing and interpreting the results of this operation has been developed in order to determine the filtration-volumetric parameters of the horizon. The method is combined as much as possible with the currently widely used graphic-analytical method. The proposed method has been shown to have substantially less restrictions on the duration of the experimental perturbation (pumping) than the currently used graphic-analytical one.